Preparation of flower-like BiOBr/Bi2WO6 Z-scheme heterojunction through an ion exchange process with enhanced photocatalytic activity. (January 2022) - Liu, Yulin; He, Jinyun; Qi, Yu; Wang, Yanwu; Long, Fei; Wang, Ming
Abstract: Flower-like BiOBr/Bi2 WO6 Z-scheme heterojunction was prepared by an ion exchange process. Bi2 WO6 was evenly coupled with BiOBr which was confirmed by structure and composition characterization. Compared with single Bi2 WO6 or BiOBr, the BiOBr/Bi2 WO6 heterojunction showed significantly enhanced photocatalytic performance in degradation of Rhodamine B (RhB), tetracycline hydrochloride (TC) and potassium dichromate (K2 Cr2 O7 ). The formation of BiOBr/Bi2 WO6 heterojunction broadened the visible light absorption range and prohibited recombination of the charge carries remarkably. The mechanism of yielding photocatalytic performance with the BiOBr/Bi2 WO6 heterojunction was proposed. Graphical abstract: Image 1 Highlights: Flower-like BiOBr/Bi2 WO6 was prepared through ion exchange process. Bi2 WO6 were composed on the outer part of BiOBr microspheres. The enhanced photocatalytic activity was ascribed to Z-scheme heterojunction. BiOBr/Bi2 WO6 improved the photocatalytic degradation activity.